Assessment of Quantitative Variation of Rajma Bean Genotypes for Yield and Yield Attributing Traits in Multi-Environments of Nepal (Global Journal of Science Frontier Research, 2021)
Rajma (Phaseolus vulgaris L) known as the common bean, French bean, kidney bean, bush bean, and pole bean is the most important grain legume of Nepal which covers about 10,529 ha areas along with the productivity of 1477 kgha-1. Generally it is grown during summer in mid/high hills and during winter (post rainy) season in terai/inner terai in rice and maize based eco-system. Now Rajma bean is being popular as the cash crop in the province 3, 5 and 6 because of producing organic products and tastier quality. Multi-environment trials was carried out at Nepalgunj, Parwanipur, Itahari and Surkhet during the winter season of 2014-2017 comprised of 10 diverse Rajma genotypes in Randomized Complete Block Design with three replications in order to evaluate the quantitative variation with respect to yield and yield contributing traits.
Keywords: component traits; environments rajma bean; quantitative; variation